F-18-fluoro-2-deoxyglucose positron emission tomography (PET) and PET/computed tomography imaging in primary staging of patients with malignant melanoma: a systematic review - Schröer-Günther, Milly A (BioMed Central, 2012)
PURPOSE: The aim of this systematic review was to systematically assess the potential patient-relevant benefit (primary aim) and diagnostic and prognostic accuracy (secondary aim) of positron emission tomography (PET) and PET/computed tomography (CT) in primary staging of malignant melanoma. This systematic review updates the previous evidence for PET(/CT) in malignant melanoma. MATERIALS AND METHODS: For the first aim, randomized controlled trials (RCTs) investigating patient-relevant outcomes and comparing PET and PET(/CT) with each other or with conventional imaging were considered. For the secondary aim, a review of reviews was conducted, which was amended by an update search for primary studies. MEDLINE, EMBASE and four databases of the Cochrane Library were searched. The risk of bias was assessed using a modified QUADAS tool. RESULTS: No RCTs investigating the patient-relevant benefit of PET(/CT) and no prognostic accuracy studies were found. Seventeen diagnostic accuracy studies of varying quality were identified. For patients with American Joint Committee on Cancer (AJCC) stages I and II, sensitivity mostly ranged from 0 to 67%. Specificity ranged from 77 to 100%. For AJCC stages III and IV, sensitivity ranged from 68 to 87% and specificity from 92 to 98%. CONCLUSION: There is currently no evidence of a patient-relevant benefit of PET(/CT) in the primary staging of malignant melanoma. RCTs investigating patient-relevant outcomes are therefore required. The diagnostic accuracy of PET(/CT) appears to increase with higher AJCC stages.